Mariposa's Song : A Novel - LaSalle, Peter (Book collections on Project MUSE., 2012)
"Pretty, twenty-year old Mariposa has entered the U.S. from Honduras by way of Nuevo Laredo, without documentation. She now serves drinks and woos customers as a B-girl--sort of a dime-a-dance arrangement--in a shabby nightclub on the east side of Austin, Texas. Rough work, it's at least giving her a start in America. Between the norteño and cumbia songs the DJ plays, a smooth-talking Anglo out-of-towner who calls himself Bill shows up at the club one Saturday night to sit and casually chat with Mariposa. He smiles and sympathizes; his flattery leads her to reveal the secret pain she has kept hidden so long. But Mariposa has no way of knowing he has secrets of his own. Even in Austin, far from the border, there are dangers more sinister than narcotraficantes or la migra."--Dust jacket flap.